Assessment of In-Vivo Antioxidant Potential of Hydro-Alcoholic Extract and Ethyl Acetate Fraction of Aerva Javanica Linn. Flowering Tops - Khunteta, Alok; Swarnkar, Surendra K; Gupta, Manish Kumar; Swarnkar, Aruna; Sharma, Swapnil; Paliwal, Sarvesh (Asian Journal of Pharmaceutical Research and Development, 2019)
Aerva javanica (Amaranthaceae) is a grey coloured woolly perennial tomentose shrub. Its traditional and folklore usage motivates further investigation on its pharmacognostic parameters and pharmacological potential. Hydro-alcoholic extract (AJCE) was prepared from flowering tops of A. javanica. In order to work further on activity guided fractions, ethyl acetate (AJEAF) fraction was prepared. Therefore, in order to establish its antioxidant potential, in-vivo effect on LPO, GSH, SOD and catalase activity was determined. For comparison, silymarin and Centella asiatica extract (CAE) were used as standard antioxidant compound/extract. Lipid peroxidation in term of MDA content expressed as nM/mg, which was 82.18 and 67.39 for AJCE with increasing doses of complete hydro-alcoholic extract (AJCE represented as AJCE-1 and AJCE-2) and 51.65 for AJEAF in contrast to 40.64 nM/mg for standard silymarin and 46.81 nM/mg for standard CAE. GSH content was determined as 3.12, 3.82 and 4.56 μg/mg wet tissue in contrast to 5.59 for standard silymarin and 4.42 for standard CAE. Superoxide scavenging was expressed as SOD U/mg wet tissue, determined as 7.26, 9.16 and 9.91 U/mg wet tissue for AJCE-1 (250 mg/kg i.p. b.w), AJCE-2 (500 mg/kg i.p. b.w), and AJEAF respectively in comparison to silymarin (10.11) and CAE (46.81 U/mg wet tissue). Catalase activity expressed as μM of H2O2 decomposed / min / mg wet tissue was determined as 0.61, 0.72 and 0.78 repectively for AJCE-1 (250 mg/kg i.p. b.w), AJCE-2 (500 mg/kg i.p. b.w), and AJEAF. Results indicated the SOD values and total antioxidant power of DEE and EAF fractions even better than standard ascorbic acid which expressed the prospective potential of fractions (DEE and EAF) against metabolic disorders.